KONTRIBUSI GAYA BELAJAR TERHADAP HASIL BELAJAR MEKANIKA TEKNIK SISWA KELAS X SMK NEGERI 1 PARIAMAN - 1119-1135 , Lilis Novitasari (Universitas Negeri Padang, 2016)
ABSTRACT The research is aimed to reveal contribution of visual, auditory and kinesthetic learning style toward learning outcomes of students on engineering mechanical subject at class X SMKN 1 Pariaman. The research is aimed to find out what style that gives the biggest contribution toward student’s learning outcome on engineering mechanical. The type of this research was ex post facto with correlation analytic approach. Population in this study was all students of class X building engineering SMKN 1 Pariaman year of school 2014/2015 which amounted to 127 students. Sample was 97 students that sorted by proportional random sampling technique. Type of data was primary and secondary data. Data analysis techniques that used in this research were: (1) data descriptive analysis, (2) analysis regulation testing, and (3) hypothesis testing. From hypothesis testing and discussion then it can be concluded that visual auditory and kinesthetic learning styles give contribution toward student’s learning outcome on mechanical engineering subject at class X building engineering SMKN 1 Pariaman. Kinesthetic learning style gives the biggest contribution. Keyword: contribution, learning style, learning outcome